Keteladanan Sifat Rasullah Muhammad SAW dalam Etika Profesi Akuntan Publik - Azis, Ilhamda (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p06, 2020)
The professional ethics of public accountants are formulated in a code of ethics. The highest source in the reference to the preparation of the code of ethics is religion. Rasulullah Muhammad SAW is the messenger of Allah Swt to spread Islam and become a role model for mankind. The study was conducted qualitatively by describing the exemplary nature of Rasulullah Muhammad SAW contained in the public accountant code of ethics compiled by IAPI, AICPA, AAOIFI. The results of the study illustrate that the exemplary nature of Rasulullah Muhammad SAW namely shidiq, amanah, tabligh, fathonah is contained in the code ethics of public accountants prepared by IAPI, AICPA, AAOIFI. Keywords: Ethics; The Nature of The Rasulullah Muhammad SAW; Public Accountants.